Highly Reconfigurable Microwave Photonic Waveform Generation Based on Time-Wavelength Interleaving - Tianzhu Zhang; Kan Wu; Junmin Xiang; Siqi Liu; Jianping Chen (IEEE Photonics Journal)
A photonic method of highly reconfigurable microwave waveform generation based on time-wavelength interleaving has been proposed and experimentally demonstrated. By modulating multi-wavelength laser sources with Mach-Zehnder modulators (MZMs), multiple Nyquist pulses corresponding to different wavelengths are generated and overlapped with each other in the time domain. A dispersion compensation fiber (DCF) is used to separate these pulses due to the wavelength dependent delay. These pulses add together after photodetection and form desired waveforms. By controlling the wavelengths and powers of multiple laser sources, we can obtain various desired waveforms with tunable repetition rates and duty cycles. Experimentally, 9 waveforms including square, triangle, sawtooth, reversed-sawtooth and trapezoid with tunable repetition rates from 3 GHz to 6 GHz and duty cycles from 20.9% to 58.4% are obtained. This work demonstrates the great potential of incoherent time-domain synthesis for highly versatile arbitrary waveform generation.